Analisis Penggunaan Barang Bukti Digital di Dalam Sistem Hukum di Indonesia (Studi Kasus Putusan Nomor 3 K/PID.SUS/2019) - Saragih, Alexandra Exelsia; Christian, Noel; Khoirunisa, Pujia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The rapid advancement of technology is also accompanied by an increasing security system in response to cybercrime that is increasing drastically. As a result, cybercrime perpetrators are always more active and faster to make new breakthroughs in the security system formed by anti-cybercrime. Evidence in cybercrime cases is divided into two criteria, namely electronic evidence and digital evidence. This study aims to test whether the evidence contained in the related case studies meets the requirements and the validity of digital evidence according to the legal system in Indonesia. In this study, a normative juridical law research method is used, namely by researching literature and laws and regulations that discuss information and electronic transactions which are then focused on examining the use of digital evidence in a case study. The results of the study show that the digital evidence in this case has met the formal and material requirements. This study also shows that there are several challenges in the process of examining digital evidence.